Market access and the concentration of economic activity in a system of declining cities - Luis Eduardo Quintero; Paula Restrepo Cadavid (REGION, 2018)
While the positive effect of market access (MA) on population and economic growth has shown to be robust, the results in the literature were obtained in a context of population growth. This article examines the impact that MA has on a system of cities that has suffered a negative population shock. An extended version of the Brezis and Krugman (1997) model of life cycle of cities predicts that a system of cities experiencing population loss will see a relative reorganization of its population from small to larger cities, increasing population concentration. Accordingly, cities with higher MA will lose relatively more. We confirm these predictions using multiple definitions of MA with a comprehensive sample of cities in Eastern Europe and Central Asia, a region with declining population growth since 1990.
Keywords: 330; Market access; urban decline; demographic transition; Eastern Europe and Central Asia